2021
DOI: 10.1590/2175-8239-jbn-2019-0242
|View full text |Cite
|
Sign up to set email alerts
|

Non-lupus full-house nephropathy: a case series

Abstract: Systemic lupus erythematosus (SLE) is a chronic multisystem autoimmune inflammatory disease. However, some patients may exhibit a histological pattern of kidney injury, with characteristics indistinguishable from lupus nephritis, but without presenting any extrarenal symptoms or serologies suggestive of SLE. Such involvement has recently been called non-lupus full-house nephropathy. The objective is to report a series of clinical cases referred to the Laboratory of the Federal University of Maranhão that recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…SLICC (The Systemic Lupus International Collaborating Clinics) used full-house staining as the sole criteria to diagnose SLE 3 . However, It has been reported that the prevalence of no-lupus full house nephropathy was 20%-30% [12][13][14][15] . "No-lupus full house nephropathy" is an umbrella term for such patients who may exhibit "lupus-like" nephropathy, but without presenting any extrarenal symptoms or serologies suggestive of SLE.…”
Section: Discussionmentioning
confidence: 99%
“…SLICC (The Systemic Lupus International Collaborating Clinics) used full-house staining as the sole criteria to diagnose SLE 3 . However, It has been reported that the prevalence of no-lupus full house nephropathy was 20%-30% [12][13][14][15] . "No-lupus full house nephropathy" is an umbrella term for such patients who may exhibit "lupus-like" nephropathy, but without presenting any extrarenal symptoms or serologies suggestive of SLE.…”
Section: Discussionmentioning
confidence: 99%
“… 3 However, it has been reported that the prevalence of no‐lupus full‐house nephropathy was 20%–30%. 12 , 13 , 14 , 15 Pathologies of full‐house nephropathy should also be considered in the differential diagnosis of SLE, including primary glomerular diseases (membranous nephropathy, C1q nephropathy, IgA nephropathy), infections (endocarditis, HIV, HBV, HCV, BK, and CMV virus), diabetes mellitus, and liver diseases. 12 , 13 , 14 This patient had none any evidence of these disease.…”
Section: Discussionmentioning
confidence: 99%
“…Non-lupus full house nephropathy is defined as having the classical findings of lupus nephritis which are positive deposits for IgG, IgA, IgM, C3, and C1q on immunofluorescence but without the other extrarenal or seologic manifestations needed for SLE diagnosis i.e ACR criteria. 1 Systemic lupus erythematosus is a multisystem autoimmune disorder. It can involve several organs with variable presentations.…”
Section: Introductionmentioning
confidence: 99%